THE DIFFERENCE AND SIMILARITIES BETWEEN ENGLISH AND UZBEK FOLKLORE (Proceedings of International Educators Conference, 2024)
This thesis explores the intricate tapestry of English and Uzbek folklore, highlighting both their distinctive characteristics and shared themes. It examines the cultural contexts that shape each tradition, revealing how historical events and societal values influence storytelling, motifs, and characters. By analyzing key narratives, proverbs, and performance practices, the study identifies common archetypes and moral lessons that transcend cultural boundaries. Ultimately, this research underscores the importance of folklore in fostering cross-cultural understanding and appreciation.